POLA KONSUMSI NON MAKANAN MAHASISWA STARA SATU (S1) REGULER FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS LAMBUNG MANGKURAT - HERMAYANTI HERMAYANTI; RIZALI RIZALI (PPJP Universitas Lambung Mangkurat, 2019)
In this journal it aims to explain and illustrate how Faculty of Economics and Business students allocate their allowances for non-food consumption expenses, based on gender and major / study programs. This research is quantitative descriptive. A sample of 93 students respondents from majors / study programs namely Management, Accounting and Economics and Development Studies (IESP) for the 2015-2017 class. The analysis technique used is descriptive statistics in averages an percentages and cross tabulation analysis. The results showed that: non-food consumption expenditure of students based on sex and department/study program had the same pattern, namely the largest expenditure for fashion spending and the smallest for tuition supports costs. Female students have the highest expenditure. on average students do expenditure in the medium category. Management students have the largest expenditure for non-food consumption followed by accounting and IESP students.Keywords: Consumption Patterns, Students, Non-Food Consumption